PENGUATAN SIKAP DISIPLIN MELALUI PENERAPAN EKSTRAKULIKULER KARAWITAN SISWA KELAS V DI SDN 1 GULANG - Rossiana Asri, Oktara; Purbasari, Imaniar; Rondli, Wawan Shokib (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
Early childhood language skills development is for children to be able to communicate verbally with the environment. Therefore, language development in early childhood is carried out using the storytelling method. It is hoped that this storytelling method can overcome student learning differences. Presenting good storytelling techniques can foster imagination and encourage students' creativity in conveying the message or information conveyed. The purpose of this article is to find out about language development strategies in early childhood education. Using the Classroom Action Research (PTK) method with data sources originating from searches. From the results of data analysis, it is known that there has been an increase in the language skills of children aged 5-6 years. Storytelling activities with hand puppets, starting from observations made in cycle I, have increased in each cycle. This can be seen from the results obtained starting from cycle I and cycle II. Where the average figure obtained in cycle I was 50.7% and in cycle II there was a significant increase of 80.5%.The results of the study show that the storytelling method using hand puppets is a suitable method for language development in early childhood education. The use of the storytelling method provides benefits for improving listening skills and the ability to broaden insight into various themes. With simple and understandable sentences. For this reason, educators are expected to play a role in the language development of early childhood children. Educators must be able to choose the right method for children's learning creatively and innovatively to help the learning process be achieved according to the objectives. Which can create a comfortable learning atmosphere so that children always feel happy and happy and don't get bored quickly.